Kesadaran Hukum Masyarakat Desa dalam Mengurus Kartu Identitas Anak di Desa Sunsea Kecamatan Naibenu Kabupaten Timor Tengah Utara - Theresia Nono; Hernimus Ratu Udju; Jenny Ermalinda (Birokrasi: JURNAL ILMU HUKUM DAN TATA NEGARA, 2024)
This research aims to determine the legal awareness of village communities in administering Child Identity Cards (CIC) and the factors inhibiting village community legal awareness in administering Child Identity Cards (CIC) in Sunsea Village, Naibenu District, North Central Timor Regency. This researcher uses qualitative research methods which in legal research are called empirical research and the research aspects consist of legal knowledge, legal understanding, legal attitudes and legal behavior. Researchers used a research location in Sunsea Village, Naibenu District, North Central Timor Regency with 30 respondents (4 Village Government, 1 BPD and 25 Community), and used primary and secondary data as types and sources of data. And the collected data is then processed using coding, editing, tabulation and analyzed systematically. The research results show that the legal awareness of village communities in processing children's identity cards in Sunsea Village, Naibenu District, North Central Timor Regency is low. This is proven by the results of research on four indicators including low legal knowledge, low understanding of the law, many people's legal attitudes that do not agree and many people's legal behavior that is not in accordance with the village community's legal awareness in managing children's identity cards (CIC). One of the internal inhibiting factors is knowledge, education and economics which tend to influence the legal awareness of village communities in processing children's identity cards, while the external inhibiting factors are the distance where the community lives and there is no cooperation between the government/certain agencies and the village government to carry out socialization.